The sovereignty of the royal portrait in revolutionary and Napoleonic Europe: five case studies surrounding Maria Carolina, Queen of Naples - Goudie, A; Allison Jessica Isabel Goudie (2014)
This study demonstrates how royal portraiture functioned during the Revolutionary and Napoleonic wars as a vehicle for visualizing and processing the contemporary political upheavals. It does so by considering a notion of the 'sovereignty of the portrait', that is, the semiotic integrity (or precisely the lack thereof) and the material territory of royal portraiture at this historical juncture. Working from an assumption that the precariousness of sovereignty which delineated the Revolutionary and Napoleonic wars goes hand in hand with the precariousness of representation during the same period, it reframes prevailing readings of royal portraiture in the aftermath of the French Revolution by approaching the genre less as one defined by the oneway propagation of a message, and more as a highly unstable intermedial network of representation. This theoretical undertaking is refracted through the figure of Maria Carolina, Queen of Naples (1752-1814), close sister and foil to Queen Marie- Antoinette of France, and who, as de facto ruler of the Kingdom of Naples, physically survived revolution but was twice dethroned and thrice exiled. A diverse ecology of royal portraiture revolving around Maria Carolina is presented across five case studies. Close attention to the materiality of a hyperrealistic wax bust of Maria Carolina reveals how portraiture absorbed the trauma of the French Revolution; Maria Carolina’s correspondence in invisible ink is used as a tool to read a highly distinctive visual language of 'hidden' silhouettes of sovereigns and to explore the in/visibility of exile; a novel reading of Antonio Canova's work for the Neapolitan Bourbons through the lens of contemporary caricature problematizes the binary between ancien régime and parvenue monarchy; and a unique miniature of Maria Carolina offers itself as a material metaphor for post-revolutionary sovereignty. Finally, Maria Carolina’s death mask testifies to how Maria Carolina herself became a relic of the ancien régime.